Utilization of rice husk ash waste and scrap aluminum as composite materials fabricated by evaporative casting - Siswanto, Rudi; Subagyo, Rachmat; Tamjidillah, Mastiadi; Mahmud, Mahmud; Setiawan, Sigit Aji (Mechanical Engineering for Society and Industry, 2024)
To achieve environmental sustainability, the integration of waste materials into new production processes is essential. This study investigates the development of aluminum matrix composites (AMCs) reinforced with rice husk ash (RHA) using the evaporative casting method. This study focuses on the effects of aluminum scrap-RHA composition, casting temperature, and styrofoam pattern thickness on key physical and mechanical properties such as fluidity length, surface roughness, hardness, and porosity. The composite material from aluminum scrap electrical cables and rice husk ash was heated in a furnace at a temperature of 900 °C for 2 hours with a sieve size of 200 mesh. The pattern material is styrofoam from electronic equipment packaging. The molding sand used is local silica sand with a sieve size of 60 mesh. The melting furnace uses a crucible furnace type with used oil as fuel. The independent variables were Al-RHA composition (100:0, 95:5, 90:10) %, pouring temperature (650 °C, 700 °C, and 750 °C), and Styrofoam pattern thickness (1, 2, 3, 4, 5, 6, and 10) mm. The results showed that the pouring temperature and the composition ratio of Al-RHA affected the fluidity length, surface roughness, hardness, and porosity, showcasing the potential of using waste materials in cost-efficient and environmentally sustainable composites for various industries.